ANALISIS DAMPAK LALU LINTAS OPERASIONAL KLINIK KECANTIKAN TERHADAP KINERJA RUAS JALAN TERDAMPAK (Universitas Bengkulu, 2025)
Traffic impact analysis is an important activity for the continuity of smooth traffic circulation with the presence of new activity centers that generate new flows. This study focuses on analyzing the impact of beauty clinic operations in South Jakarta on several road sections that are considered to have an impact. There are four road sections that are analyzed. Traffic performance analysis in this study uses the PKJI 2023 method to determine the capacity of the road section and continues to determine the level of road service according to the Minister of Transportation's PM number 96 of 2015. After analyzing traffic performance based on the results of the traffic census, the existing conditions in 2024 were found to have road sections at levels B and C. To determine future traffic predictions, a further analysis was also carried out, namely the calculation of predicted services after 5 years of clinic operations with existing traffic growth conditions. The results of the analysis show that the level of road service has decreased to level F in the next 5 years. From the results of the analysis, the recommendations given are in the form of planning for the construction of flyovers and the development of public transportation network services that can be accessed by consumers of the beauty clinic. Keywords: analysis of traffic, PKJI 2023, road performance, forescasting